Health beneficial properties of spirulina in preventing non-communicable diseases - the green metabolic regulator from the sea - Ekeuku, Sophia Ogechi; Ima-Nirwana Soelaiman,; Chin, Kok-Yong (Penerbit Universiti Kebangsaan Malaysia, 2021)
Spirulina is a type of cyanobacteria containing various micro- and macronutrients and has been used as a functional food. Due to its nutritional components, spirulina possesses antioxidant and anti-inflammatory properties, which can potentially prevent non-communicable diseases (NCDs) triggered by inflammation and oxidative stress. This review aims to provide an overview of the effects of spirulina supplementation on NCDs derived from cellular, animals, and human studies. The current literature generally showed that spirulina could protect against NCDs, such as metabolic disorders, osteoporosis, gastric ulcer, hepatic, renal, and neurological disorders. These beneficial effects were mediated through the antioxidant and anti-inflammatory effects of spirulina and seem to be dependent on dose and duration of treatment. Despite the abundance of preclinical studies, human clinical trials validating the effects of spirulina on NCDs are lacking. These preclinical findings warrant a proper clinical trial to evaluate the efficacy and safety of spirulina supplementation in protecting human against NCDs.